Addressing the rights and well‐being of domestic workers in Africa: Status in Malawi - Symon Fidelis Nayupe; Alieu Touray; Dalitso Tembo; Mama Tamanda Msiska; Juliana Mputeni; Allan Hans Muhome (Wiley, 2023)
Abstract Domestic work continues to contribute to employment in most developing countries significantly. Over 75.6 million people are domestic workers worldwide, three‐quarters of whom are women. In Africa, many people still rely on domestic work for employment, making up 2.2% of the total workforce on the continent. With a predominant presence in the sub‐Saharan region, Africa's domestic workforce is estimated at around 9.6 million. Mirroring the global trend, most workers are women, with an estimated 15.8% of Africa's paid female employees being domestic workers. This considerable presence of domestic work contributes to domestic and intra‐continental migration in Africa, where about 80% of the domestic workers are from within. The Southern African region is a major intra‐continent destination for most workers. In Malawi, domestic labour is also common and is one of the country's primary sources of jobs, especially for poor populations who often domestically migrate from rural to urban areas. However, country estimates for the total number of domestic workers are yet to be published. Although there have been improved work conditions for domestic workers in some countries worldwide, the situation is different in many African nations, including Malawi. Domestic workers still face underpayment, long working hours, physical and psychological ill‐treatment from employers, challenging, harsh working environments and lack of access to healthcare. We discuss the status of the well‐being of domestic workers in Malawi, a country in southeastern Africa. We note that the working conditions for domestic workers continue to be unfavourable, with physical and psychological abuse and other human rights violations. To improve the well‐being and working conditions of domestic workers, government and non‐governmental organisations should, among other things, facilitate programmes to root out poverty, strengthen the legal framework that addresses domestic worker abuse and ensure social protection, including healthcare protection.